HENRY MURRAY: THE PERSON AND THEIR STRUCTURE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
So far, there is no unified view or approach in psychology regarding the nature, structure, and regularities of personality development. This lack of consensus affects the use of diagnostic, prognostic, and therapeutic methods. Existing knowledge remains fragmented and unstructured; there is no consistent understanding of the structure and elements of personality, the stages and mechanisms of its development, or its systemic qualities and functions. This article presents the views of Henry Murray, a representative of the neopsychoanalytic school, on personality and its structure.